An fMRI investigation of the effects of attempted naming on word retrieval in aphasia - Heath, Shiree; McMahon, Katie L.; Nickels, Lyndsey A.; Angwin, Anthony; MacDonald, Anna D.; van Hees, Sophia; McKinnon, Eril; Johnson, Kori; Copland, David A. (Frontiers in Human Neuroscience, 2015)
In healthy controls, picture naming performance can be facilitated by a single prior exposure to the same picture (“priming”). This priming phenomenon is utilized in the treatment of aphasia, which often includes repeated picture naming as part of a therapeutic task. The current study sought to determine whether single and/or multiple exposures facilitate subsequent naming in aphasia and whether such facilitatory effects act through normal priming mechanisms. A functional magnetic resonance imaging (fMRI) paradigm was employed to explore the beneficial effects of attempted naming in two individuals with aphasia and a control group. The timing and number of prior exposures was manipulated, with investigation of both short-term effects (single prior exposure over a period of minutes) and long-term effects (multiple presentations over a period of days). Following attempted naming, both short-term and long-term facilitated items showed improvement for controls, while only the long-term condition showed benefits at a behavioral level for the participants with aphasia. At a neural level, effects of long-term facilitation were noted in the left precuneus for one participant with aphasia, a result also identified for the equivalent contrast in controls. It appears that multiple attempts are required to improve naming performance in the presence of anomia and that for some individuals with aphasia the source of facilitation may be similar to unimpaired mechanisms engaged outside the language network.